Emerging Religious Practices and their impact on women: An analysis of the case of MEC for Health, Limpopo vs Rabalago and Another 2018 (4) SA 270 (LP) - Maureen Mswela (Prof); Priccilar Vengesai (LLD) (Pharos Journal of Theology)
South Africa, like other nations on the African continent, has been plagued by a range of disturbing narratives concerning religious observances that expose humanity to numerous detrimental effects. We encountered the egregious religious practice of administering Doom insecticide to congregants purportedly for therapeutic and demonic exorcism purposes, as exemplified in the case of MEC for Health, Limpopo vs Rabalago and Another. In this matter, the Limpopo Province’s Department of Health sought a judicial interdict to prohibit Prophet Rabalago’s controversial religious practice, aimed at safeguarding public health. The importance of delineating the case at hand for our discourse lies in the High Court's ruling, which signifies a pivotal triumph in the endeavour to eradicate perilous religious practices targeting vulnerable congregants. This discourse employs a qualitative research methodology, primarily anchored in a document study complemented by observational techniques. The objectives of this paper are to elucidate the findings derived from the court case, to critique these findings through a gendered lens, and to proffer recommendations for the protection of women and other susceptible congregants against injurious religious practices in South Africa. Furthermore, this paper advocates for the establishment of a stringent regulatory framework for the registration of ecclesiastical organisations. Upon registration, the founding members would pledge to eschew participation in religious practices that inflict harm upon women and other at-risk groups. The State must put compliance measures with a possibility of deregistration upon defiance.